Emergence of new psychoactive substance 2-fluorodeschloroketamine: Toxicology and urinary analysis in a cluster of patients exposed to ketamine and multiple analogues. (July 2020) - Tang, Magdalene H.Y.; Li, Terence C.; Lai, C.K.; Chong, Y.K.; Ching, C.K.; Mak, Tony W.L.
Highlights: 2-Fluorodeschloroketamine (2F-DCK) is a newly emerged psychoactive substance. This ketamine analogue was identified in multiple poisoning patients. 2F-DCK was found to have similar metabolic and clinical profiles as ketamine. Alarmingly, most patients had co-exposure to ketamine and multiple of its analogues. Abstract: New psychoactive substances (NPS) emerge continually, amongst which is a growing class of ketamine analogues with an arylcyclohexylamine backbone. Recently we reported a poisoning outbreak associated with 2-oxo-PCE (deschloro- N -ethyl-ketamine). The present report describes the emergence of another ketamine analogue, 2-fluorodeschloroketamine (2F-DCK). The compound was first detected in a patient's urine, its identity confirmed by accurate mass analysis and comparison with reference standard. Four putative metabolites were identified, including nor-2F-DCK, dehydronor-2F-DCK (major metabolite) and two hydroxylated derivatives of nor-2F-DCK. Between January and July 2019, 20 cases of analytically confirmed 2F-DCK exposure were encountered. In 19 out of 20 cases, at least one more ketamine-type drug was detected concurrently with 2F-DCK, including ketamine (90%), deschloroketamine (DCK, 50%), 2-oxo-PCE (45%) and tiletamine (10%). In particular, six of the cases showed the presence of 4 ketamine-type drugs in the same urine sample. The clinical effects observed in patients exposed to 2F-DCK are predominantly neurological (impaired consciousness, agitation, abnormal behaviour) and cardiovascular (hypertension, tachycardia); five patients had loss of consciousness or convulsion. Management was mainly supportive; all patients recovered uneventfully. This is the first clinical case series involving 2F-DCK and frontline medical personnel are urged to be aware of this rapidly expanding class of NPS, in particular the co-ingestion of multiple ketamine analogues.